Genome-wide association study reveals mechanisms underlying dilated cardiomyopathy and myocardial resilience - Jurgens, Sean J.; Rämö, Joel T.; Kramarenko, Daria R.; Wijdeveld, Leonoor F. J. M.; Haas, Jan; Chaffin, Mark D.; Garnier, Sophie; Gaziano, Liam; Weng, Lu-Chen; Lipov, Alex; Zheng, Sean L.; Henry, Albert; et al. (Nature genetics, 2024)
Dilated cardiomyopathy (DCM) is a heart muscle disease that represents an important cause of morbidity and mortality, yet causal mechanisms remain largely elusive. Here, we perform a large-scale genome-wide association study and multitrait analysis for DCM using 9,365 cases and 946,368 controls. We identify 70 genome-wide significant loci, which show broad replication in independent samples and map to 63 prioritized genes. Tissue, cell type and pathway enrichment analyses highlight the central role of the cardiomyocyte and contractile apparatus in DCM pathogenesis. Polygenic risk scores constructed from our genome-wide association study predict DCM across different ancestry groups, show differing contributions to DCM depending on rare pathogenic variant status and associate with systolic heart failure across various clinical settings. Mendelian randomization analyses reveal actionable potential causes of DCM, including higher bodyweight and higher systolic blood pressure. Our findings provide insights into the genetic architecture and mechanisms underlying DCM and myocardial function more broadly.
Gesehen am 10.04.2025